TiO2/NiO hybrid shells: p–n junction photocatalysts with enhanced activity under visible light. Issue 41 (22nd September 2015) - Wang, Minggui; Hu, Yimin; Han, Jie; Guo, Rong; Xiong, Huixin; Yin, Yadong
Abstract : Mesoporous hybrid shells of TiO2 /NiO were prepared by sequential coating of TiO2 and NiO on SiO2 nanospheres through a combined sol–gel and hydrothermal process followed by calcination and template removal. Abstract : Mesoporous hybrid shells of TiO2 /NiO were prepared by sequential coating of TiO2 and NiO on SiO2 nanospheres through a combined sol–gel and hydrothermal process followed by calcination and template removal. Evaluation of visible light photocatalytic activities in dye degradation and H2 production demonstrated their superior performance, which could be attributed to the porous nature of the hybrid shells and the enhanced charge separation and visible-light absorption associated with the introduction of NiO.